A Review of Resistive Switching Devices: Performance Improvement, Characterization, and Applications. Issue 4 (9th April 2021) - Shi, Tuo; Wang, Rui; Wu, Zuheng; Sun, Yize; An, Junjie; Liu, Qi
Abstract : Resistive Switching Devices Resistive switching device is an emerging device with the advantages of simple structure, easy for 3D integration, low power consumption, high speed, and good scalability. The resistive switching can be primarily attribute to formation of conductive filaments in the bulk or interfacial effects. After integration in a crossbar structure (e.g., 1T1R, 1S1R or 3D VRRAM), various applications can be further explored. Due to the stochastic nature and the capability of data storage and computation, resistive switching device is a promising fundamental device for memory, computation, security applications and so on. More details can be found in article number 2000109 by Qi Liu and co‐workers.